Is primary dysmenorrhea affected by gray matter volumetric changes in the brain? - Kaplan, Ela; Kaplan, Selçuk (The European Research Journal, 2023)
Objectives: We aimed this study to investigate the relationship between gray matter volume differences women who suffer from primary dismenorrea (PD) and asymptomatic women. Methods: Brain magnetic resonance (MRI) imaging of 113 PD patients and 113 healthy women were performed. The volume of gray matter structures was calculated with the VolBrain automatic calculation system. Results: Cut-off values were found by ROC analysis for right, left and total volumes in both groups. A caudate lobe volume above 6.33 cm3 is 99.1% sensitive and 77.9% specific for a diagnosis of PD. In addition, the volumes of other pain-related gray matter regions were decreased in PD patients (p < 0.001). Conclusions: Atrophic changes in the medial GM structures in the brain in women with PD may cause hyperalgesia and the quantitative determination of these morphological changes may play an important role in the diagnosis of PD.